If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4k + 0) = 10k + -2(k + -7) Reorder the terms: 3(0 + 4k) = 10k + -2(k + -7) Remove the zero: 3(4k) = 10k + -2(k + -7) Remove parenthesis around (4k) 3 * 4k = 10k + -2(k + -7) Multiply 3 * 4 12k = 10k + -2(k + -7) Reorder the terms: 12k = 10k + -2(-7 + k) 12k = 10k + (-7 * -2 + k * -2) 12k = 10k + (14 + -2k) Reorder the terms: 12k = 14 + 10k + -2k Combine like terms: 10k + -2k = 8k 12k = 14 + 8k Solving 12k = 14 + 8k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-8k' to each side of the equation. 12k + -8k = 14 + 8k + -8k Combine like terms: 12k + -8k = 4k 4k = 14 + 8k + -8k Combine like terms: 8k + -8k = 0 4k = 14 + 0 4k = 14 Divide each side by '4'. k = 3.5 Simplifying k = 3.5
| 4x^2-3x+13=9x+8 | | x/9-16=115 | | 3/14x=-5/2 | | 8-4v=56 | | x^2+6xy+y^2+32=0 | | 6a+10b= | | 20*15+10y=300 | | 50+4(x-2)=310 | | 0.5*x=3 | | 48/62 | | 20*10+10y=300 | | 4(5x+6)=-22+6 | | 1/2cos2x | | 20*5+10y=300 | | x^4-49x^2+2401=0 | | 10-(3y-5)=1-4y | | 3u+-7=-13 | | -2x+23=2x+11 | | 2x+3x-1+2x+3x-1= | | 4(k-6)=2(k+2) | | 5(3m-2)-(m-3)=13-4(-4m+5) | | 10-(2z-6)=4-3z | | 6a+3=2a-13 | | 4.4y=-88 | | -6x+56=-9-31 | | 2(-3)=76 | | 9.2y=-88 | | 0.71*x=3 | | 2n+5=(n-2)-n | | 8=2x-3y | | 3(3v-2)=4(2v+2) | | 2X+1-4=-2X-34 |